Personalized community-based prehabilitation for a high-risk surgical patient opting for pylorus-preserving pancreaticoduodenectomy: a case report. (2nd December 2021) - A. van Beijsterveld, Christel; Bongers, Bart C.; den Dulk, Marcel; Dejong, Cornelis H.; van Meeteren, Nico L.
ABSTRACT: Introduction : Prehabilitation aims for an optimal physical functioning level before, during, and after hospitalization for major surgery. The purpose of this case report was to illustrate the care pathway of a high-risk patient who opted for pylorus-preserving pancreaticoduodenectomy, including preparation for this procedure by participating in a community-based exercise prehabilitation program. The report describes patient examination, evaluation in decision-making for surgery, the prehabilitation program, and outcomes within the context of the Hypothesis-Oriented Algorithm for Clinicians II. Case Description : The patient was a 75-year-old woman with a history of several comorbidities and a polypoid mass in the descending segment of the duodenum. Based on the preoperative assessment, the level of physical functioning was expected to be insufficient to cope adequately with the stress of hospitalization and surgery. Intervention : A 4-week prehabilitation program, including aerobic, resistance, and functional task training in a community-based physical therapy practice. Outcomes : Prehabilitation had a beneficial impact on improving functional mobility preoperatively (timed up-and-go test score improved from 19.4 to 10.0 s, five times sit-to-stand test score improved from 30.1 to 10.1 s, and two-minute walk test distance improved from 55.0 to 107.0 m). Surgery and postoperative recovery proceeded without complications. She achieved independent physical functioning on postoperative day 6 and was discharged home on postoperative day 12. Conclusion : Preoperative risk-assessment can support clinical decision-making in a high-risk patient opting for major abdominal surgery. Furthermore, a remarkable improvement in physical functioning can be achieved by community-based prehabilitation in a high-risk surgical patient.